A national riparian restoration programme in New Zealand: Is it value for money?. (1st February 2017) - Daigneault, Adam J.; Eppink, Florian V.; Lee, William G.
Abstract: National scale initiatives are being attempted in New Zealand (NZ) to meet important environmental goals following land-use intensification over recent decades. Riparian restoration to filter agricultural spillover effects is currently the most widely practised mitigation measure but few studies have investigated the cumulative value of these practices at a national level. We use an applied economic land use model the benefits (GHG emissions, N leaching, P loss, sedimentation and biodiversity gain) and relevant costs (fencing, alternative stock water supplies, restoration planting and opportunity costs) of restoring riparian margins (5–50 m) on all streams in NZ flowing through current primary sector land. Extensive sensitivity analysis reveals that depending on margin width and cost assumptions, riparian margin restoration generates net benefits of between NZ$1.7 billion – $5.2 billion/yr and benefit-cost ratios ranging between 1.4 and 22.4. This suggests that even when not monetising the increase in biodiversity or components of stream ecosystem health and other benefits from planting riparian strips, the benefits to climate and freshwater are significantly greater than the implementation costs of riparian restoration. Highlights: An economic land use model analyses benefits and costs of riparian planting in New Zealand. A national-level planting initiative could yield net benefits of NZ$1.7 billion – $5.2 billion/yr. 65 of 72 scenarios yielded positive net benefits from planting buffers on primary sector land. In some cases, benefits outweighed costs by a margin of more than 20 to 1.